Long-term Outcome After Percutaneous Endoscopic Gastrostomy in Children - Fu-Yu Wu; Jia-Feng Wu; Yen-Hsuan Ni (Pediatrics and Neonatology)
Percutaneous endoscopic gastrostomy (PEG) is widely accepted as the preferred procedure to establish long-term enteral feeding. Objective: To learn the long-term outcomes of the patients who have undergone PEG placement, we reviewed our experience with children who underwent this procedure in our institute. Methods: A total of 83 pediatric patients (42 males and 41 females), who were aged from 3 months to 20 years, underwent PEG insertion in National Taiwan University Hospital from January 2000 to April 2011. The underlying diseases of the patients receiving PEG were neurological dysfunction (n = 67), metabolic disorders (n = 9), gastrointestinal disease (n = 2), and congenital heart disease (n = 1). This procedure was performed under intravenous sedation or under general anesthesia. Prophylactic antibiotics were administered for 1 day. Tube feeding began 24 hours after the PEG placement. The body weight of the patients was recorded 1 day before PEG placement and at least 6 months after PEG placement. Results: The weight-for-age Z-score before and at 6 months after PEG placement were −1.5 ± 2.0 and −0.9 ± 2.1, respectively, which was statistically significant (paired t test, p = 0.006). The catch-up growth was recorded after PEG placement. Complications of PEG in our patients included cellulitis at the gastrostomy wound (n = 14), dislodgement of the tube (n = 17), and persistent gastrocutaneous fistula (n = 3). The PEG tube was removed permanently in seventeen patients because they resumed an adequate oral intake. During the follow-up period, 14 patients died of an underlying disease or infection. Conclusion: Our experience confirmed that PEG placement is a good long-term route for nutritional supply with no serious complications in children.